2020
DOI: 10.46568/pjgs.v20i1.425
|View full text |Cite
|
Sign up to set email alerts
|

Resilience And Aggression Of Adolescents, Early And Middle-Aged Adults: Analyzing Gender Differences

Abstract: The present study aimed to analyze gender difference in resilience and aggression of three developmental stages (adolescence, early adulthood, and middle adulthood). For this, comparative research design was utilized. Through purposive sampling, 600 participants (Mage = 28.24 years, SD = 12.12) with males and females equal in number; were selected from different regions of Karachi, Pakistan. Participants’ demographic information was collected through Respondent Information Form. Resilience and aggression were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…A positive relationship was found between gender and students’ positive resilience in the SEM model. Male students scored higher than female students for resilience, which matches that of prior studies [ 57 , 58 ], which also found that resilience was significantly higher in males. The reason for this finding could be that girls are generally more emotional than boys so they could be affected more deeply after experiencing adversity or challenges.…”
Section: Discussionsupporting
confidence: 90%
“…A positive relationship was found between gender and students’ positive resilience in the SEM model. Male students scored higher than female students for resilience, which matches that of prior studies [ 57 , 58 ], which also found that resilience was significantly higher in males. The reason for this finding could be that girls are generally more emotional than boys so they could be affected more deeply after experiencing adversity or challenges.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with previous work indicating that low resilience is associated with a decreased capability to deal with stress [ 34 ]. In contrast, males have been reported to have greater resilience during adolescence and early adulthood than females, but differences disappear in older adulthood [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resilience is a multidimensional trait characterized by the factors of engagement, adaptability, control, competence, and sense of humor to cope with stressful circumstancies (Hurtes & Allen, 2001;De Caroli & Sagone, 2014). Gender differences in resilience are evident: Italian girls score higher than boys in control and engagement (De Caroli & Sagone, 2014); Italian boys score higher than girls in sense of humor, competence, and adaptability, while girls score higher than boys in engagement (Sagone & De Caroli, 2016); Pakistan boys obtain higher scores than girls in resilience (Sarwar et al, 2010;Naseem & Munaf, 2020); Spanish boys score higher than girls in confidence and negative cognition in the Self-Domain using the Adolescent Resilience Questionnaire (Guilera et al, 2015); in addition, Italian males reach higher scores in positive attitudes than females, whereas females obtain higher scores in alienation than males using the Dispositional Resilience Scale (Prati, 2010).…”
Section: Introductionmentioning
confidence: 99%